Lysine Demethylase KDM4A Associates with Translation Machinery and Regulates Protein Synthesis - Van Rechem, Capucine (Cancer Discov, 2015)
Chromatin modifying enzymes are predominantly nuclear; however, these factors are also localized to the cytoplasm and very little is known about their role in this compartment. In this report, we reveal a non-chromatin linked role for the lysine-specific demethylase KDM4A. We demonstrate that KDM4A interacts with the translation initiation complex and impacts the distribution of translation initiation factors within polysome fractions. Furthermore, KDM4A depletion reduced protein synthesis and enhanced the protein synthesis suppression observed with mTOR inhibitors, which paralleled an increased sensitivity to these drugs. Lastly, we demonstrate that JIB-04, a JmjC demethylases inhibitor, suppresses translation initiation and enhances mTOR inhibitor sensitivity. These data highlight an unexpected cytoplasmic role for KDM4A in regulating protein synthesis and suggest novel potential therapeutic applications for this class of enzyme.